2021
DOI: 10.3389/fncel.2020.581950
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence Highlighting the Importance of Redox Dysregulation in the Pathogenesis of Amyotrophic Lateral Sclerosis (ALS)

Abstract: The cellular redox state, or balance between cellular oxidation and reduction reactions, serves as a vital antioxidant defence system that is linked to all important cellular activities. Redox regulation is therefore a fundamental cellular process for aerobic organisms. Whilst oxidative stress is well described in neurodegenerative disorders including amyotrophic lateral sclerosis (ALS), other aspects of redox dysfunction and their contributions to pathophysiology are only just emerging. ALS is a fatal neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 393 publications
(291 reference statements)
0
14
0
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease categorized by progressive loss of upper and lower motor neurons [ 1 ]. It affects the motor neurons of the cerebral cortex, brainstem, and spinal cord in adults [ 2 4 ]. Individuals with ALS live with continuous and multiple functional losses, presenting upper, lower, and trunk muscle atrophy, muscle weakness, fasciculation, and subsequently progressive loss of all movements [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease categorized by progressive loss of upper and lower motor neurons [ 1 ]. It affects the motor neurons of the cerebral cortex, brainstem, and spinal cord in adults [ 2 4 ]. Individuals with ALS live with continuous and multiple functional losses, presenting upper, lower, and trunk muscle atrophy, muscle weakness, fasciculation, and subsequently progressive loss of all movements [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS can damage neurons [ 58 ], and the ability of neuronal cells to maintain their normal redox state diminishes during aging [ 59 ]. Substantial evidence supports the critical importance of redox homeostasis in normal functioning of the nervous system [ 60 ], and redox dysregulation contributes to numerous neurodegenerative diseases [ 61 ]. Moreover, declining neuronal mitochondrial respiratory capacity may also contribute to NMJ degeneration, as Hayes et al have reported an age-dependent loss of mitochondria from motor neurons in Sod1 -/- mice [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial bioenergetics can also be affected in ALS [ 186 ]. According to this, examination of the ventral horn and the spinal motor neurons of ALS patients showed a significant decrease in MT-ND2 (Complex I) and MT-CO3 (Complex IV) genes, which could lead to the inhibition of ATP synthesis and motor neuronal degeneration [ 186 188 ]. Importantly, impairment of mitochondrial dynamics has been found in ALS, generating motor neuron toxicity and degeneration [ 19 , 185 , 189 , 190 ].…”
Section: Mitochondrial Dysfunction In Ad Pd Hd and Alsmentioning
confidence: 99%